Toxic Epidermal Necrolysis After Exposure to Dithiocarbamate Fungicide Mancozeb - Zakharov, Sergey; Csomor, Jan; Urbanek, Petr; Pelclova, Daniela (Basic & clinical pharmacology & toxicology, 2016)
Toxic epidermal necrolysis (TEN) is a life-threatening mucocutaneous disease with high mortality. Dithiocarbamates (DTC) are organosulphur compounds widely used in agriculture, industry and households. We report a case of TEN after exposure to mancozeb in fungicide. A 48-year-old 75 kg b.w. man was admitted with fever and generalized skin/mucous lesions after application of fungicide in a home garden. The patient had necrotic desquamation of gastrointestinal/respiratory tract mucosa, ocular lesion and skin epidermolysis of 90% of body surface. The laboratory findings included elevation of inflammatory parameters, hyperglycaemia, increased urea, creatinine, liver enzymes, hypoalbuminemia and electrolyte disturbances. The treatment included supportive care, management of fluid/electrolyte requirements, analgesics and enteral nutrition. Skin lesions were treated with occlusive non-adhesive biological wound dressings. Due to the proof of Acinetobacter, Escherichia coli and Escherichia faecalis from skin swabs, a combination of meropenem with amikacin was administered. During the next 2 weeks, complete re-epithelialization of skin lesions occurred, mucosal lesions healed and the laboratory parameters returned to normal. The patient was discharged on day 42. TEN is a rare condition that is generally caused by medications. Nevertheless, high attention should be paid to the cases of occupational or household exposure to DTC fungicides widely used in agriculture and home gardens because of their ability to cause TEN after skin and inhalation exposure. Greater emphasis on the hazardous properties of these products is necessary to ensure non-professional users are aware of the necessity of protective clothing during mixing, loading, application and early re-entry into treated fields.
Keywords: Fungicides, Industrial; zineb; maneb; Humans; lidé středního věku; Maneb; průmyslové fungicidy; vystavení vlivu životního prostředí; výsledek terapie; Gardening; lidé; Stevens-Johnson Syndrome; Stevensův-Johnsonův syndrom; Zineb; zahradničení; Male; Middle Aged; Treatment Outcome; Environmental Exposure; mužské pohlaví